2023
DOI: 10.1039/d3sm00053b
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol)/sodium alginate/magnetite composites: magnetic force microscopy for tracking magnetic domains

Abstract: Hydrogels of poly(vinyl alcohol) (PVA)/sodium alginate (SA), and magnetic nanoparticles (MNPs) were prepared by solvent casting in the absence and in the presence of magnets, in order to obtain MNPs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Table 2 showed that the number of live fibroblasts significantly increased after 48 and 72 h culture onto the hydrogels containing PG, VG or PG-VG compared to the PVA alone. These results are comparable to those generated with chitosan-rich PVA hydrogels (Huang et al, 2023) or sodium alginate (Alavarse et al, 2023), to list only a few. It is important to note that this is the first study designing cannabis-product-rich hydrogels and evaluating their safety.…”
Section: Skin Fibroblasts Proliferated Once In Culture On the Thc-ric...supporting
confidence: 84%
“…Table 2 showed that the number of live fibroblasts significantly increased after 48 and 72 h culture onto the hydrogels containing PG, VG or PG-VG compared to the PVA alone. These results are comparable to those generated with chitosan-rich PVA hydrogels (Huang et al, 2023) or sodium alginate (Alavarse et al, 2023), to list only a few. It is important to note that this is the first study designing cannabis-product-rich hydrogels and evaluating their safety.…”
Section: Skin Fibroblasts Proliferated Once In Culture On the Thc-ric...supporting
confidence: 84%
“…Magnetic hydrogels have demonstrated significant potential in the field of neural tissue engineering. These materials can respond to external magnetic field, which facilitates the favorable growth of cells on the hydrogel matrix. , In a recent study, we reported that magnetic coatings of SA/PVA/MNPs containing aligned MNPs were rougher, decreasing the proliferation of HT-22 neural cells . Magnetic SA/PVA hydrogels were also successfully applied for Fenton degradation of organic dyes …”
Section: Introductionmentioning
confidence: 99%
“…49,50 In a recent study, we reported that magnetic coatings of SA/PVA/MNPs containing aligned MNPs were rougher, decreasing the proliferation of HT-22 neural cells. 51 Magnetic SA/PVA hydrogels were also successfully applied for Fenton degradation of organic dyes. 52 In this study, SA/PVA compositions both in the absence and presence of MNPs at concentrations of 1.0, 2.5, and 5.0 mg/ mL were subjected to 3D printing and subsequently crosslinked using Ca 2+ ions via postspraying.…”
Section: Introductionmentioning
confidence: 99%